Prognostic Value of Multiple Draining Lymph Node Basins in Melanoma: A Matched-Pair Analysis Based on the John Wayne Cancer Institute Experience - J. Harrison Howard (Frontiers in Oncology, 2017)
BackgroundThe prognostic significance of multiple draining basins is controversial in melanoma because analyses have not adequately controlled for standard prognostic variables. We hypothesized that an analysis based on prognostically matched pairs of patients with multiple versus single drainage basins would clarify any independent role of basin number.Study designWe identified patients in our 40-year prospective database, who underwent preoperative lymphoscintigraphy, intraoperative sentinel node biopsy and wide local excision for cutaneous melanoma. Overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS) were compared in patients with multiple versus single drainage basins after matching by age, sex, Breslow depth, primary site, and stage at diagnosis.ResultsWe identified 274 patients with multibasin drainage and 1,413 patients with single draining lymph node basins. Matching yielded 259 pairs (226 trunk, 27 head/neck, 6 extremity). Among matched pairs, multibasin drainage did not affect rates of lymph node metastasis (p = 0.84), OS (p = 0.23), DSS (p = 0.53), overall recurrence (p = 0.65), locoregional recurrence (p = 0.58), or distant recurrence (p = 1.0). Multivariable analysis linked higher T stage, ulceration, older age, and lymph node positivity to decreased DSS (p < 0.01) and DFS (p < 0.001). Number of drainage basins was not significant on univariable or multivariable analysis.ConclusionThis analysis, the first to match for standard prognostic factors, suggests that multiplebasin drainage as identified by lymphoscintigraphy has no independent biological or prognostic significance in primary cutaneous melanoma.